Effect of using social media on word of mouth advertising for tourism industry - ANDERVAZH, LEILA; ALBONAIEMI, EBRAHIM; ZARBAZOO, MARSHA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aimed to investigate the impact of using social media on word of mouth advertising with an emphasis on the mediating role of brand equity in the tourism industry‏. The purpose of this study is applied type and in terms of the method is a survey. ‏The data gathering tool in this study is the standard questionnaire of Andrew. In this study, face and content validity were used to evaluate the validity of the questionnaire. Findings of a critical ratio value (T-value ranging from -1.96 to 1.96) resulted in a 99% be positive and significant. RESUMEN Este estudio tuvo como objetivo investigar el impacto del uso de las redes sociales en la publicidad boca a boca con énfasis en el papel mediador del valor de la marca en la industria del turismo. El propósito de este estudio es el tipo aplicado y en términos del método es una encuesta. La herramienta de recopilación de datos en este estudio es el cuestionario estándar de Andrew. En este estudio, se utilizó la validez aparente y de contenido para evaluar la validez del cuestionario. Los resultados de un valor de relación crítica (valor T que varía de -1,96 a 1,96) dieron como resultado un 99% de ser positivo y significativo.